Publish or Perish! Challenges and Strategies in Publishing Research Papers in Top Tier Academic Journals - Polas , Mohammad Rashed Hasan (Journal of Business & Management, 2024)
This paper explores the pivotal benefits of publishing in top-tier academic journals for graduate students and academics. It delves into the challenges researchers encounter in this pursuit, examining the current landscape marked by intense competition, evolving open-access paradigms, and diverse journal requirements. The journey to publication entails meticulous manuscript preparation, engagement with peer review, and a nuanced understanding of the editorial process. For graduate students and academics, publication not only validates their work but also contributes to career advancement and the collective knowledge base. Facilitating student publication involves fostering a research culture, mentorship, research opportunities, and collaboration. Initiating the publishing journey requires defining a research question, conducting a literature review, and selecting an appropriate journal. The writing phase demands precision, engagement, and adherence to guidelines, while the submission and revision process involves careful submission and strategic responses to feedback. Challenges include competition, rigorous peer review, and evolving open-access dynamics. Navigating these challenges necessitates early career planning, selecting the right journal, collaborative research, and ethical considerations. The conclusion underscores the importance of persistence and resilience in overcoming challenges, positioning researchers for success in the peaks of academic publishing